Psychometric properties of measurements obtained with the Marlowe–Crowne Social Desirability Scale in an Icelandic probability based Internet sample - Vésteinsdóttir, Vaka; Reips, Ulf-Dietrich; Joinson, Adam; Thorsdottir, Fanney (Computers in Human Behavior, 2015)
Internet surveys have become a very popular research tool. Relatively little attention has, however, been devoted to the possible changes in psychometric properties when measurements are obtained with Internet surveys. The Marlowe–Crowne Social Desirability Scale (MCSDS) is the most widely used instrument for measuring the tendency to respond in a socially desirable way and is often used to validate other measures. The purpose of the current research is to evaluate the dimensionality and reliability of measurements obtained with the MCSDS and short forms of the scale in an Internet sample of the general public in Iceland. An e-mail invitation was sent to a sample of 1200 panel members drawn from the Social Science Research Institute (SSRI) probability based panel, of those 536 participants completed all items on the MCSDS. Reliability estimates were in line with results from previous studies (α = .81 for the MCSDS data and α ranging from .59 to .75 for short forms). Using confirmatory factor analysis, a good fit was obtained for a one-factor model of measurements obtained with the MCSDS and its short forms (apart from significant chi square values in all cases but one), which generally supports the assumption of unidimensionality. published